Evaluation of normal distribution of palpebral fissure among the medical and paramedical students of Eastern Nepal - Surendra Kumar Sah; Deepak Chaudhary; Subrato Ghosh; Amit Kumar Shah (Asian Journal of Medical Sciences, 2022)
Background: The palpebral fissure (PF) is the space between the upper and lower eyelids when the eye is open. The bilateral orbital region which is located in the face acts as one of the important determinants in the perception of facial attractiveness, youthfulness, and health conditions of the individuals. The PF dimensions may get altered in cases of facial deformities and road traffic traumas. Aims and Objectives: The aim of this study was to analyze the mode of distribution of PF dimensions in medical and paramedical students in correlation with gender. Materials and Methods: The study was a cross-sectional study conducted in the duration of August 2021–November 2021 including the sample of 300 medical and paramedical students in an equal number of male and female of age group 16–22 years from Nobel Medical College Teaching Hospital, Biratnagar, Nepal. We measured the dimensions of PF during the normal gaze. The data analysis was done using the SPSS version 16. Results: The mean length of PF (LPF) in males and females was 23.24 mm and 22.72 mm, respectively. The mean height of PF (HPF) in male and female was 8.52 mm and 8.60 mm, respectively. The difference between males and females LPF and HPF was significant (<0.05). The mean PF index (PFI) in male and female subjects was, respectively, 37.20 and 38.68 which were statistically significant. Conclusion: It was found that the LPF and HPF were more in males and PFI was slightly more in females than the male which confirms the sexual dimorphism. The data obtained will be helpful in the esthetic consideration of the student’spersonality as well.